Generational Shift in Learning Discomfort: A Systematic Literature Review of Pedagogical Tensions Between Millennials and Generation Z - Suyono; Sugiarti; Winarjo, Wahyudi (Professorline, 2025)
This study aims to map the development of scientific studies on pedagogical tensions between Millennials and Generation Z in the context of formal and digital learning. This study employs a Systematic Literature Review (SLR) approach, following the PRISMA protocol. A total of 115 scientific articles indexed in the Scopus database from 2019 to 2024 were analyzed using bibliometric tools VOSviewer and CiteSpace. The results indicate six main clusters in the literature on intergenerational pedagogical tension: (1) culture and perception; (2) learning experiences and generational differences; (3) communication and intergenerational activities; (4) development of digital content and media; (5) Gen Z consumer behavior and local values; and (6) strategies and institutional support. Keywords such as generation, student, education, and medium emerged as central nodes in the literature network, highlighting the importance of generational and media aspects in learning dynamics. Additionally, topics such as trust, intention, and belief also show an increasing trend in recent publications, indicating a shift in focus toward affective and psychological aspects in digital education. This study contributes to expanding intergenerational education research through a visual bibliometric approach and provides a conceptual foundation for developing inclusive and adaptive pedagogical strategies tailored to the characteristics of digital-native generations like Gen Z. The main limitation of this study is its focus on articles in the Scopus database, which does not include literature from other databases such as Web of Science or Google Scholar. Therefore, further research is recommended to expand the scope of data and deepen exploration of practical dimensions in the implementation of intergenerational pedagogy.